1981
DOI: 10.2527/jas1982.5361424x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Floor Temperature, Supplemental Heat and Drying at Birth on Neonatal Swine1

Abstract: The objective was to determine the effects of floor temperature (20 or 30 C), supplemental heat (heat lamp or light bulb) and drying at birth on piglet survival to day 5. Rectal and infrared skin temperatures were taken on 326 piglets for the first 8 hr postpartum. Blood samples were obtained at birth, day 2 and day 5 and analyzed for thyroxine (T4), triiodothyronine (T3) and cortisol by radioimmunoassay. Weight of each pig was recorded at birth and on days 1, 2, and 5. Survival rates were monitored daily. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
1

Year Published

1985
1985
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 0 publications
5
22
1
Order By: Relevance
“…In pigs, its changes have been described in detail e.g. in context with changes in the thermal environment (Holub 1958;L:ivicka et al 1960;Lyhs et al 1969;McGinnis et al 1981). Recently introduced measurement of skin temperatures over various parts of body surface by means of thermistor probes provides average temperature values, however, without an accurate distribution pattern and time dynamics of these changes.…”
Section: Thermography Thermal Environment Piglets Heat Sourcementioning
confidence: 99%
“…In pigs, its changes have been described in detail e.g. in context with changes in the thermal environment (Holub 1958;L:ivicka et al 1960;Lyhs et al 1969;McGinnis et al 1981). Recently introduced measurement of skin temperatures over various parts of body surface by means of thermistor probes provides average temperature values, however, without an accurate distribution pattern and time dynamics of these changes.…”
Section: Thermography Thermal Environment Piglets Heat Sourcementioning
confidence: 99%
“…Litters raised in cooler environments (10 to 20 C) experience higher mortality due to chilling (Taylor et al, 1952;Parker et al, 1980;McGinnis et al, 1981 ;Nienaber et al, 1985). Although piglets are able to increase heat production by increasing their metabolic rate at an air temperature of 20 C, the pig's lack of insulation, sparse pelage and a large surface area-to-body weight ratio handicaps the pig in maintaining homeostasis (Mount, 1968;McGinnis et al, 1981). Therefore, we speculate that increased mortality at 18 C may have been due to chilling of piglets (sow feed intake was normal), but at 30 C increased mortality may have been due to reduced sow feed intake and reduced milk production.…”
Section: Discussionmentioning
confidence: 99%
“…From the evidence it is clear that drying piglets can result in lower mortality however, a simpler method may be to place the piglet under a heat lamp (Andersen et al, 2009). Drying piglets with stimulation without combination of other strategies was only assessed in four studies (Christison et al, 1997;McGinnis et al, 1981;Pan, 1995;and Vasdal et al, 2011), of which one study did not record mortality (Pan, 1995), one study showed no effects on mortality and two showed an improvement in mortality where piglets were dried (Christison et al, 1997;and Vasdal et al, 2011). A further two studies included drying as part of an "advanced care" around farrowing which included a number of interventions (Dewey et al, 2008;and White et al, 1996).…”
Section: Clinical Scenariomentioning
confidence: 99%
“…However, maximal care litters did end up heavier at 16 days with no impact on mortality between groups (Dewey et al, 2008). Another study with multiple treatments looked at the impacts of drying piglets with a paper towel, the addition of supplemental heat and two different floor temperatures on growth and thermoregulation (McGinnis et al, 1981). Within this study piglets which were dried had higher rectal temperatures at 1 hour old and higher skin temperatures at 30 minutes and 1 hour of age (McGinnis et al, 1981).…”
Section: Appraisal Application and Reflectionmentioning
confidence: 99%